The Progression of Alzheimer's Disease: Are Fast Decliners Really Fast? A Four-Year Follow-Up. - Barocco, Federica; Spallazzi, Marco; Concari, Letizia; Gardini, Simona; Pelosi, Annalisa; Caffarra, Paolo (J Alzheimers Dis, 2017)
BACKGROUND: The rate of cognitive and functional decline in Alzheimer's disease (AD) changes across individuals. OBJECTIVES: Our purpose was to assess whether the concept of "fast decline" really fits its definition and whether cognitive and functional variables at onset can predict the progression of AD. METHODS: 324 AD patients were included. We retrospectively examined their Mini-Mental State Examination (MMSE) total score and sub-items, Activities of Daily Living (ADL), and Instrumental Activities of Daily Living (IADL) at baseline and every six months for a 4-year follow-up. Patients were divided into "fast decliners" (n = 62), defined by a loss ≥5 points on the MMSE score within the first year from the baseline; "intermediate decliners" (n = 37), by a loss ≥5 points after the first year and before the 18th month; or "slow decliners" (n = 225), composed of the remaining patients. RESULTS: At baseline, the groups did not differ on demographic, clinical, and cognitive variables. The decline at the end of the 4-year follow-up period seems to be similar among the different decline clusters. Predictors of disease progression have not been identified; only the MMSE total score at 12 months <14/30 was indicative of a poor prognosis. CONCLUSIONS: Even with the limitation due to the small sample size, the lack of differences in the disease progression in time in the different clusters suggest the inconsistency of the so-called "fast decliners". This study was unable to show any significant difference among clusters of AD progression within a 4-year time interval. Further studies should better clarify whether a more consistent distinction exists between slow and fast decliners.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Cognition Disorders; Disease Progression; Female; Humans; Longitudinal Studies; Male; Psychiatric Status Rating Scales; ROC Curve; Time Factors